A new species of Erythroxylum (Erythroxylaceae) from Colombia and emendation of Erythroxylum plowmanianum - Jara, Orlando Adolfo (Phytotaxa, 2015)
The description of Erythroxylum plowmanianum is emended, and the new species Erythroxylum cogolloi is described. Both species are endemics to the sub-montane forest of Colombia’s Middle Magdalena River Basin. Diagnostic characters are discussed, notes on distribution and illustration are provided for each species.